The Role of Balance Scorecard and Management Information Systems in Decision Making Through Company Performance - Khaidar, Akromul; Taufiq, Abd. Rohman (Universitas Negeri Surabaya, 2025)
This study aims to analyze the Implementation of Balance Scorecard (BSC) and Management Information System on investment decision making through company performance. BSC as a performance management tool provides a comprehensive view of financial and non-financial aspects that are relevant to investment decision making through company performance, while Management Information System (MIS) supports the decision-making process by providing accurate and relevant information. The results of the study indicate that Key Performance Indicators (KPI) and MIS indicators have a significant influence on investment decision making, while performance assessment is unable to mediate BSC and MIS in investment decision making. BSC as a performance management tool provides a comprehensive view of financial and non-financial aspects that are relevant to decision making, while MIS supports the decision-making process by providing accurate and relevant information. Effective BSC and MIS indicators can improve the quality of more accurate and comprehensive investment decisions. The implications of this study support the importance of integrating both tools in strategic decision making in companies.